Penggunaan Aplikasi Hris Dan Mydamri Sebagai Sistem Pendukung Basis Data Kepegawaian Pada Perusahaan Umum Damri (Fakultas Ekonomi Universitas Gresik, 2023)
Changes in the development of technology to digital, forcing companies to make adjustments to the technology itself. Digital competence is a need for companies today to be able to fulfill their functional responsibilities, without closing the possibility of obstacles from some parties who cannot keep up with this development quickly. This study aims to analyze the use of HRIS (Human Resource Information System) and MyDAMRI applications as a support system for the DAMRI Public Company (Perum) staffing database. This type of research is descriptive research using a qualitative approach. Data collection techniques are carried out using 2 (two) ways, namely: 1) observation and 2) data collection in the form of images and writings. The results of this study show that this data-based application provides many benefits for employees and companies and facilitates work for the human resources division in the company